MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MELALUI MODEL PROBLEM BASED LEARNING BERMEDIA E-MODUL PADA PESERTA DIDIK SMKN 2 BOJONEGORO - Muhammad Faisal Kurniawan (Universitas Muhammadiyah Gresik, 2023)
The purpose of this research is to enhance students' critical thinking skills using the Problem Based Learning (PBL) model with Electronic Modules (E-modules) in the subject of Pancasila Education, specifically focusing on the topic of Rights and Responsibilities as School Citizens, Community Members, and Citizens of the Nation. This study is a Classroom Action Research conducted in two cycles, each consisting of four stages: action planning, implementation, data collection, and reflection. The research subjects were 36 male students from class X-TKRO-1 at SMKN 2 Bojonegoro. Data was collected through tests and observations, and the data analysis used descriptive statistical analysis techniques. The research findings indicate that the implementation of the PBL model with e-modules can improve students' critical thinking skills, as evidenced by the improvement in each indicator. The number of students with good critical thinking skills increased from the first cycle to the second cycle, with 11.1% in the excellent category, 22.2% in the good category, 27.8% in the satisfactory category, and 5.5% in the poor category.